Giant photon bunching, superradiant pulse emission and excitation trapping in quantum-dot nanolasers - Jahnke, Frank; Gies, Christopher; Aßmann, Marc; Bayer, Manfred; Leymann, H. A. M.; Foerster, Alexander; Wiersig, Jan; Schneider, Christian; Kamp, Martin; Höfling, Sven (Nature Communications)
Light is often characterized only by its classical properties, like intensity or coherence. When looking at its quantum properties, described by photon correlations, new information about the state of the matter generating the radiation can be revealed. In particular the difference between independent and entangled emitters, which is at the heart of quantum mechanics, can be made visible in the photon statistics of the emitted light. The well-studied phenomenon of superradiance occurs when quantum–mechanical correlations between the emitters are present. Notwithstanding, superradiance was previously demonstrated only in terms of classical light properties. Here, we provide the missing link between quantum correlations of the active material and photon correlations in the emitted radiation. We use the superradiance of quantum dots in a cavity-quantum electrodynamics laser to show a direct connection between superradiant pulse emission and distinctive changes in the photon correlation function. This directly demonstrates the importance of quantum–mechanical correlations and their transfer between carriers and photons in novel optoelectronic devices.

Ultrasonic transmission measurements in the characterization of viscoelasticity utilizing polymeric waveguides - Bause, Fabian; Rautenberg, Jens; Feldmann, Nadine; Webersen, Manuel; Claes, Leander; Gravenkamp, Hauke; Henning, Bernd (Measurement Science and Technology)
Keywords: material characterization; material parameters; acoustic waveguide; daming; ultrasonic transducer

Determination of the material properties of polymers using laser-generated broadband ultrasound - Claes, Leander; Meyer, Thorsten; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (Journal of Sensors and Sensor Systems)

Miniaturized all-optical Sound Pressure Sensor - Fischer, Balthasar; Claes, Leander (INTER-NOISE 2016)

Increasing the Sensitivity of Impedance with Respect to Material Parameters of Triple-Ring Electrode Piezoelectric Transducers using Algorithmic Differentiation - Jurgelucks, Benjamin; Claes, Leander

Optimisation of triple-ring-electrodes on piezoceramic transducers using algorithmic differentiation - Jurgelucks, Benjamin; Claes, Leander (AD2016 The 7th International Conference on Algorithmic Differentiation)

Characterization of Continuous-fiber Reinforced Thermoplastics Using Thermoacoustically Excited Ultrasonic Lamb Waves - Webersen, Manuel; Johannesmann, Sarah; Claes, Leander; Henning, Bernd (2016 IEEE IUS~Proceedings)

Vergleich zweier Verfahren der Unsicherheitsabschätzung bei linearisierten inversen Problemen mittels Bayes’scher Inferenz und Pseudoinverse am Beispiel akustischer Transmissionsmessung - Feldmann, Nadine; Bause, Fabian; Henning, Bernd (Sensoren und Messsysteme 2016)

Uncertainty estimation for linearised inverse problems comparing Bayesian inference and a pseudoinverse approach for acoustic transmission measurements - Feldmann, Nadine; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)

Experteninterviews mit Schulleiterinnen und Schulleitern an rheinland-pfälzischen Schwerpunktschulen – Erste Einblicke in den Prozess der qualitativen Inhaltsanalyse - Scheer, David (Bildungs- und Erziehungsorganisationen im Spannungsfeld von Inklusion und Ökonomisierung)

Einbindung von Oﬀshore Windenergie durch innovative Prognosemodelle und Speichertechnologien - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (14. Symposium Energieinnovation 2016)

Green Energy from the Ocean An overview on costeffectiv and reliable measuring systems - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

Bestimmung der relevanten klimatologischen Parameter Oﬀshore - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Wissenschaftliche Verhandlungen 2016 der Deutschen Physikalischen Gesellschaft Regensburg)

Systemvergleich zur zeitlich und örtlich hochaufgelösten Einstrahlungsmessung - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Wissenschaftliche Verhandlungen 2016 der Deutschen Physikalischen Gesellschaft Regensburg)

Shadowing Investigations on Thin Film Modules - Krauter, Stefan; Wendtland, S.; Weber, T.; Berghold, J.; Grunow, Paul (Proceedings of the 31st European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 20.–24. Juni 2016, S. 2265–2270.)

Start-Up Factory Kumasi (Ghana) – Paderborn (Germany): Smart Tropical House KNUST, Kumasi, Ghana - Klaus, Tobias; Schmitz, E.A.; Klusmann, B.; Piper, M.; Krauter, Stefan; Rongen, L.; Gruber, R.; Nkrumah, I.; Ampong, K.; Donkor, M.; Tamakloe, R. (Proceedings of the 31st European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 20.–24. Juni 2016, S. 3048–3049)

Deviations of results for energy yield from efficiency rankings of micro-inverters - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 31st European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 20.–24. Juni 2016, S. 1508–1511)

Photovoltaics and the Energy System: Adaptation of layout and load. - Kazmerski, L.; Renne, D; Kazem, H.; Sopian, D.K.; Al-Bastaki, N.; Haji, S.; Mohd, D.; Othman, Y.H.; Hoffmann, W.; Krauter, Stefan; Swift-Hook, D.T.; Book, T. (Renewable Energy in the Service of Mankind Vol II)

Experimental study of phase change materials for photovoltaic modules: Energy performance and economic yield for the EPEX spot market - Japs, Ewald; Sonnenrein, Gerrit; Krauter, Stefan; Vrabec, Jadran (Solar Energy)

Short term wind and energy prediction for offshore wind farms using neural networks - Balluff, Stefan; Bendfeld, Jörg; Krauter, Stefan (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

S2CX: From relational data via SQL/XML to (Un-)Compressed XML - Böttcher, Stefan; Hartel, Rita; Wolters, Dennis (Information Systems)

Modeling Cross-Device Systems with Use Case Diagrams - Wolters, Dennis; Gerth, Christian; Engels, Gregor (Proceedings of the CAiSE'18 Forum at the 28th International Conference on Advanced Information Systems Engineering (CAiSE'16))

Towards Applying Model-based Testing in Test Case Migration - Jovanovikj, Ivan; Güldali, Baris; Grieger, Marvin (Softwaretechnik-Trends)

Reengineering of Legacy Test Cases: Problem Domain & Scenarios - Jovanovikj, Ivan; Grieger, Marvin; Güldali, Baris; Teetz, Alexander (Softwaretechnik-Trends, Proceedings of the 3rd Workshop Model-Based and Model-Driven Software Modernization (MMSM))

Friendship Processes in Network Creation Games - Kutzias, Damian

Routing Algorithms on Delayed Networks for Disaster Management Support - Schaefer, Johannes Sebastian

Inklusion in der beruflichen Bildung - Kremer, H.-Hugo; Büchter, K.; Buchmann, U. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Asymptotically Optimal Gathering on a Grid - Cord-Landwehr, Andreas; Fischer, Matthias; Jung, Daniel; Meyer auf der Heide, Friedhelm (arXiv:1602.03303)
In this paper, we solve the local gathering problem of a swarm of $n$ indistinguishable, point-shaped robots on a two dimensional grid in asymptotically optimal time $\mathcal{O}(n)$ in the fully synchronous $\mathcal{FSYNC}$ time model. Given an arbitrarily distributed (yet connected) swarm of robots, the gathering problem on the grid is to locate all robots within a $2× 2$-sized area that is not known beforehand. Two robots are connected if they are vertical or horizontal neighbors on the grid. The locality constraint means that no global control, no compass, no global communication and only local vision is available; hence, a robot can only see its grid neighbors up to a constant $L_1$-distance, which also limits its movements. A robot can move to one of its eight neighboring grid cells and if two or more robots move to the same location they are merged to be only one robot. The locality constraint is the significant challenging issue here, since robot movements must not harm the (only globally checkable) swarm connectivity. For solving the gathering problem, we provide a synchronous algorithm -- executed by every robot -- which ensures that robots merge without breaking the swarm connectivity. In our model, robots can obtain a special state, which marks such a robot to be performing specific connectivity preserving movements in order to allow later merge operations of the swarm. Compared to the grid, for gathering in the Euclidean plane for the same robot and time model the best known upper bound is $\mathcal{O}(n^2)$.

Multiobjective Optimal Control Methods for the Development of an Intelligent Cruise Control - Dellnitz, Michael; Eckstein, Julian; Flaßkamp, Kathrin; Friedel, Patrick; Horenkamp, Christian; Köhler, Ulrich; Ober-Blöbaum, Sina; Peitz, Sebastian; Tiemeyer, Sebastian (Mathematics in Industry)

On the computation of attractors for delay differential equations - Ziessler, Adrian; Molo, Mirko Hessel-Von; Dellnitz, Michael (Journal of Computational Dynamics)

Placement of Services with Flexible Structures Specified by a YANG Data Model - Dräxler, Sevil; Karl, Holger (Proceedings of the 2nd International IEEE Conference on Network Softwarization (NetSoft))
Network function virtualization and software-defined networking allow services consisting of virtual network functions to be designed and implemented with great flexibility by facilitating automatic deployments, migrations, and reconfigurations for services and their components. For extended flexibility, we go beyond seeing services as a fixed chain of functions. We present a YANG model for describing the service structure in deployment requests in a flexible way that enables changing the order of functions in case the order of traversing them does not affect the functionality of the service. Upon receiving such requests, the network orchestration system can choose the optimal composition of service components that gives the best results for placement of services in the network. This introduces new complexities to the placement problem by greatly increasing the number of possible ways a service can be composed. In this paper, we describe a heuristic solution that selects a Pareto set of the possible compositions of a service as well as possible combinations of different services, with respect to different resource requirements of the services. Our evaluations show that the selected combinations consist of representative samples of possible structures and requirements and therefore, can result in optimal or close-to-optimal placement results.

Physical attacks on pairing-based cryptography - Günther, Peter

Patterns for Constructing Mutation Operators: Limiting the Search Space in a Software Engineering Application - Kühne, Thomas; Hamann, Heiko; Arifulina, Svetlana; Engels, Gregor (Proceedings of the 19th European Conference on Genetic Programming (EuroGP 2016))
We apply methods of genetic programming to a general problem from software engineering, namely example-based generation of specifications. In particular, we focus on model transformation by example. The definition and implementation of model transformations is a task frequently carried out by domain experts, hence, a (semi-)automatic approach is desirable. This application is challenging because the underlying search space has rich semantics, is high-dimensional, and unstructured. Hence, a computationally brute-force approach would be unscalable and potentially infeasible. To address that problem, we develop a sophisticated approach of designing complex mutation operators. We define ‘patterns’ for constructing mutation operators and report a successful case study. Furthermore, the code of the evolved model transformation is required to have high maintainability and extensibility, that is, the code should be easily readable by domain experts. We report an evaluation of this approach in a software engineering case study.

Lang/Weidmüller: Genossenschaftsfesetz. Gesetz betreffend des Erwerbs- und Wirtschaftsgenossenschaften (Kommentar) 38. Auflage - Krimphove, Dieter (Zeitschrift für das gesamte Genossenschaftswesen ZFGG)

Intradomain Allosteric Network Modulates Calcium Affinity of the C-Type Lectin Receptor Langerin - Hanske, Jonas; Aleksić, Stevan; Ballaschk, Martin; Jurk, Marcel; Shanina, Elena; Beerbaum, Monika; Schmieder, Peter; Keller, Bettina G.; Rademacher, Christoph (Journal of the American Chemical Society)
Keywords: pc2-ressources

PAndA 2 : Analyzing Permission Use and Interplay in Android Apps (Tool Paper) - Jakobs, Marie-Christine; Töws, Manuel; Pauck, Felix (Workshop on Formal and Model-Driven Techniques for Developing Trustworthy Systems)
We present PAndA2, an extendable, static analysis tool for Android apps which examines permission related security threats like overprivilege, existence of permission redelegation and permission flows. PAndA2 comes along with a textual and graphical visualization of the analysis result and even supports the comparison of analysis results for different android app versions.

Ontology-based representation of abstract optimization models for model formulation and system generation - Stapel, Florian

Sprint Diagnostic with RTK-GPS & IMU Sensor Fusion - Cedric Mertens, Jan

Implementation of Bilinear Pairings on Reconfigurable Hardware - Nassery, Abdul Sami

Acceleration of EMTP for Distribution Networks on Data Flow Machines using the Latency Insertion Method - Amin, Omair

Boolean Difference Based Reliability Evaluation of Fault Tolerant Circuit Structures on FPGAs - Anwer, Jahanzeb; Platzner, Marco (Euromicro Conference on Digital System Design (DSD))

A novel immersive augmented reality system for prosthesis training and assessment - Boschmann, Alexander; Dosen, Strahinja; Werner, Andreas; Raies, Ali; Farina, Dario (Proc. IEEE Int. Conf. Biomed. Health Informatics (BHI))

Adaptive playouts for online learning of policies during Monte Carlo Tree Search - Graf, Tobias; Platzner, Marco (Journal Theoretical Computer Science)

Beschleunigte Simulation elektrischer Stromnetze mit GPUs - Horstmann, Jens

Optimal Generation Dispatch of Distributed Generators Considering Fair Contribution to Grid Voltage Control - Ma, Chenjie; Kaufmann, Paul; Töbermann, J.-Christian; Braun, Martin (Renewable Energy)

Operating System Support for Reconfigurable Cache - Makeswaran, Vignesh

Private/Shared Data Classification and Implementation for a Multi-Softcore Platform - Ibne Ashraf, Ishraq

Thread Shadowing: On the Effectiveness of Error Detection at the Hardware Thread Level - Meisner, Sebastian; Platzner, Marco (Reconfigurable Computing and FPGAs (ReConFig), 2016 International Conference on)

Konzeption und Implementierung einer digitalen Ansteuerung für den Betrieb einer elektrischen Sendereinheit für induktive Energieübertragung - Schmidt, Marco

Applications of Evolutionary Computation - 19th European Conference, EvoApplications - Squillero, Giovanni; Burelli, Paolo; M. Mora, Antonio; Agapitos, Alexandros; S. Bush, William; Cagnoni, Stefano; Cotta, Carlos; De Falco, Ivanoe; Della Cioppa, Antonio; Divina, Federico; Eiben, A.E.; I. Esparcia-Alcázar, Anna; et al.